Law : key concepts in philosophy - Ingram, David, 1952- (Key concepts in philosophy., 2006)
Key Concepts in Philosophy is a series of concise, accessible and engaging introductions to the core ideas and subjects encountered in the study of philosophy. Specially written to meet the needs of students and those with an interest in, but little prior knowledge of, philosophy, these books open up fascinating, yet sometimes difficult ideas. The series builds to give a solid grounding in philosophy and each book is also ideal as a companion to further study. The philosophy of law - inquiry into the origins, nature and theory of laws and legal principles, and those concepts that structure the.